Recent progresses and challenges in aqueous lithium–air batteries relating to the solid electrolyte separator: A mini-review - Chen, Peng; Bai, Fan; Deng, Jun wen; Liu, Bin; Zhang, Tao (Frontiers in Chemistry, 2022)
The lithium–air (Li–air) battery utilizes infinite oxygen in the air to store or release energy through a semi-open cathode structure and bears an ultra-high theoretical energy density of more than 1,000 Wh/kg. Therefore, it has been denoted as the candidate for next-generation energy storage in versatile fields such as electric vehicles, telecommunications, and special power supply. Among all types of Li–air batteries, an aqueous Li–air battery bears the advantages of a high theoretical energy density of more than 1,700 Wh/kg and does not have the critical pure oxygen atmosphere issues in a non-aqueous lithium–air battery system, which is more promising for the actual application. To date, great achievements have been made in materials’ design and cell configurations, but critical challenges still remain in the field of the solid electrolyte separator, its related lithium stripping/plating at the lithium anode, and catholyte design. In this mini-review, we summarized recent progress related to the solid electrolyte in aqueous Li–air batteries focusing on both material and battery device development. Moreover, we proposed a discussion and unique outlook on improving solid electrolyte compatibility and battery performance, thus designing an aqueous Li–air battery with higher energy density and better cycle performance in the future.